2016
DOI: 10.17109/azh.62.4.355.2016
|View full text |Cite
|
Sign up to set email alerts
|

No effect of a glyphosate-based herbicide on larval dragonflies (Aeshna cyanea) and adult newts (Lissotriton vulgaris) in a laboratory-based experiment

Abstract: Pesticides can exert negative effects on aquatic organisms at very low concentrations. While several prey taxa are frequently used as models in ecotoxicology studies, there is little information about the pesticide-sensitivity of predators. We examined the effects of a frequently applied glyphosate-based herbicide on two common aquatic predators: larval Aeshna cyanea dragonflies and adult male Lissotriton vulgaris newts, which are top predators in ephemeral water bodies lacking fishes. We exposed predators to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Other studies on amphibians indicated increased excretion of defensive chemicals in the common toads (Bufo bufo) upon exposure throughout larval development to Glyphogan Classic R (360 g/l glyphosate-the same composition as Roundup Classic R , 41.5 w/w% glyphosate and 15.5 w/w% POEA) at a level corresponding to 4 mg/l glyphosate concentration (Bókony et al, 2017;Miko Z. S et al, 2017a) and behavioral changes of adult newts (Lissotriton vulgaris) in response to exposure to Glyphogan Classic R at levels corresponding to 2 and 6.5 mg/l glyphosate concentration (Mikó Z. et al, 2017b), even though the same research group previously reported no observable effects on L. vulgaris with Glyphogan Classic R at a final glyphosate concentration of 6.5 mg/l (Ujszegi et al, 2015(Ujszegi et al, , 2016. In artificial pond mesocosm experiments exposure to the generic glyphosate-based herbicide GLY-4 Plus affected mortality, body size, cellular immune response and tail morphology of the larvae of the spotted salamander Ambystoma maculatum in an UV-B radiation dependent manner (Levis and Johnson, 2015), and similar effects were observed on the blue ridge two-lined salamander Eurycea wilderae as well (Gandhi and Cecala, 2016).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 98%
“…Other studies on amphibians indicated increased excretion of defensive chemicals in the common toads (Bufo bufo) upon exposure throughout larval development to Glyphogan Classic R (360 g/l glyphosate-the same composition as Roundup Classic R , 41.5 w/w% glyphosate and 15.5 w/w% POEA) at a level corresponding to 4 mg/l glyphosate concentration (Bókony et al, 2017;Miko Z. S et al, 2017a) and behavioral changes of adult newts (Lissotriton vulgaris) in response to exposure to Glyphogan Classic R at levels corresponding to 2 and 6.5 mg/l glyphosate concentration (Mikó Z. et al, 2017b), even though the same research group previously reported no observable effects on L. vulgaris with Glyphogan Classic R at a final glyphosate concentration of 6.5 mg/l (Ujszegi et al, 2015(Ujszegi et al, , 2016. In artificial pond mesocosm experiments exposure to the generic glyphosate-based herbicide GLY-4 Plus affected mortality, body size, cellular immune response and tail morphology of the larvae of the spotted salamander Ambystoma maculatum in an UV-B radiation dependent manner (Levis and Johnson, 2015), and similar effects were observed on the blue ridge two-lined salamander Eurycea wilderae as well (Gandhi and Cecala, 2016).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 98%
“…In most studies, animals decreased the amount of uncontaminated food consumed or increased the time to forage or feed on uncontaminated food after pre-exposure [145,146,153,154]. However, increases in food consumption after GBH exposure were also documented [147][148][149], while other studies showed that pre-exposure had no effect on feeding behavior [152,155,156]. Some predators (primarily wolf spiders) became hyperactive after exposure to GBH but less coordinated, improving their catches per minute but increasing the number of lunges required for each catch [149,150].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies indicate that GBH exposure alters feeding behavior, others do not. For instance, in a study involving two predators, the southern hawker dragonfly, Aeshna cyanae and smooth newt, Lissotriton vulgaris, the predatory activity of organisms exposed to GBH, chronically or acutely, was no different from those unexposed, suggesting that GBH had no effect on the foraging of the predators [155,156].…”
Section: Foraging and Feeding Behaviormentioning
confidence: 99%
“…Such is the case for the surfactant polyethoxylated tallowamine (POEA), whose cytotoxic effect has been evidenced in some studies (Székács & Darvas, 2018). In contrast, other studies have reported that glyphosate is safe for bees (Fagúndez et al ., 2016), dragonflies (Ujszegi et al ., 2016), predators (Hassan et al ., 1988; Saska et al ., 2017) and parasitoids (Carmo et al ., 2010). This dichotomy is not limited to glyphosate.…”
Section: Introductionmentioning
confidence: 99%